Hannah Arendt and the uses of history : imperialism, nation, race, and genocide - King, Richard H. 1942- Hrsg; Stone, Dan 1971- (Berghahn Books, 2007)
Introduction / Richard H. King and Dan Stone -- Imperialism and colonialism -- Race power, freedom, and the democracy of terror in German racialist thought / Elisa von Joeden-Forgey -- Race thinking and racism in Hannah Arendt's The Origins of Totalitarianism / Kathryn T. Gines -- When the real crime began : Hannah Arendt's The Origins of Totalitarianism and the dignity of the western philosophical tradition / Robert Bernasconi -- Race and bureaucracy revisited : Hannah Arendt's recent reemergence in African studies / Christopher J. Lee -- On pain of extinction : laws of nature and history in Darwin, Marx, and Arendt / Tony Barta -- Nation and race -- The refractory legacy of decolonization : revisiting Arendt on violence / Ned Curthoys -- Anti-semitism, the bourgeoisie, and the self-destruction of the nation-state / Marcel Stoetzler -- Post-totalitarian elements and Eichmann's mentality in the Yugoslav War and mass killings / Vlasta Jalušič -- Intellectual genealogies and legacies -- Hannah Arendt on totalitarianism : moral equivalence and degrees of evil in modern political violence / Richard Shorten -- Hannah Arendt, biopolitics, and the problem of violence : from animal laborans to homo sacer / André Duarte -- The 'subterranean stream of Western history' : Arendt and Levinas after Heidegger / Robert Eaglestone -- Hannah Arendt and the old 'new science' / Steven Douglas Maloney -- The Holocaust and 'the human' / Dan Stone -- Conclusion : "Arendt between past and future" / Richard H. King